The moderating effect of investment opportunities on the relation between analyst coverage and managerial myopia: evidence from Egypt - Shimaa Abdel-Moniem Abdel-Khalik; Mohamed E. Abulezz; Ahmed M. Shaker Samaan (Cogent Business & Management, 2024)
The purpose of this study is to investigate whether analyst coverage is associated with managerial myopia. Moreover, the effect of the interaction between analyst coverage and investment opportunities on managerial myopia is also investigated. We used data of 100 companies listed on the Egyptian stock exchange for the period 2014–2019. The results indicate that analyst coverage exacerbates managerial myopia. This result is consistent with the financial analysts’ pressure role, which indicates that analyst coverage imposes excessive pressure on managers to achieve short-term goals and thereby exacerbates managerial myopia. Furthermore, this study finds that the interaction between analyst coverage and investment opportunities alleviates managerial myopia. This result is consistent with the financial analysts’ monitoring role, which suggests that financial analysts, by acting as effective monitors, mitigate managerial myopia.